Design and Implementation of an Android-Based Competency Test Registration Application - Iwan Setiawan (NEXCORE: Journal of Computer Science & Intelligent Systems, 2026)
Computer technology and information systems are developing rapidly in line with the increasing demand for information. Advances in technology require that human activities which still rely on manual writing tools and are less efficient be transformed through modern technological solutions. At present, the registration process for competency tests at the Computer Laboratory Technical Implementation Unit (UPT) is still conducted manually by filling out forms provided by the head of the UPT and making direct payments. The purpose of this research is to develop an Android-based Competency Test Registration Application for the Computer Laboratory Technical Implementation Unit, so that student registrations can be carried out online and more effectively. In this study, the author employed data collection techniques including observation, interviews, and literature review. The programming language used is PHP with a MySQL database, while the system development method applied is Rapid Application Development (RAD), which consists of three stages: Requirement Planning, RAD Workshop Design, and Implementation. Additionally, the Unified Modeling Language (UML) was utilized as a design tool to facilitate the application development process.